MiR-34a-5p Negatively Regulates Oxidative Stress on Lens Epithelial Cells by Silencing GPX3 – A Novel Target. (4th May 2022) - Wang, Song; Yu, Mengsi; Yan, Hong; Liu, Jun; Guo, Chenjun
Abstract: Purpose: MiR-34a-5p is reported to be related with age-related nuclear cataract. This study investigated the mechanism of miR-34a-5p in the regulation of oxidative stress on lens epithelial cells. Methods: The three candidate miRNAs were screened by CCK-8 assays after transfection of mimics or inhibitor in H2 O2 -treated HLE-B3 cells. The apoptosis, ROS level and GPX activity of HLE-B3 cells transfected with miR-34a-5p mimics or inhibitor were analysed by flow cytometry, cellular ROS and GPX activity test. The target genes of miR-34a-5p were predicted by proteomic and bioinformatic analysis. The relationship between miR-34a-5p and GPX3 were internally validated by qRT-PCR and Western blot and externally verified by dual-luciferase reporter assay. The effect of miR-34a-5p-GPX3 axis on regulation of oxidative stress in HLE-B3 cells were conducted by overexpression of GPX3 and tested by flow cytometry analysis, cellular ROS and GPX detection. Results: The viability of H2 O2 -treated HLE-B3 cells were weakened by up-regulated miR-34a-5p. Cell apoptosis and oxidative damage were also induced by overexpression of miR-34a-5p. GPX3 and SRC were identified as target genes of miR-34a-5p by combined analysis of proteomic and bioinformatics, while GPX3 was selected for further research for its connection with anti-oxidation. Western blot and qRT-PCR tests proved that GPX3 is negatively regulated by miR-34a-5p. Dual-luciferase reporter assay verified that GPX3 is the direct target of miR-34a-5p. The increased oxidative stress induced by transfection of miR-34a-5p mimics in H2 O2 -treated HLE-B3 cells was attenuated by overexpression of GPX3. Conclusions: MiR-34a-5p is a negative regulator of oxidative stress on lens epithelial cells and the mechanism is by silencing the expression of GPX3. These data suggest that miR-34a-5p may be a potential novel therapeutic target for the prevention and treatment of age-related cataract.